Gold-Catalyzed Cyclization of 2-Alkynylaldehyde Cyclic Acetals via Hydride Shift for the Synthesis of Indenone Derivatives - Yamada, Tsuyoshi; Park, Kwihwan; Tachikawa, Takumu; Fujii, Akiko; Rudolph, Matthias; Hashmi, A. Stephen K.; Sajiki, Hironao (Organic letters, 2020)
An efficient gold-catalyzed cyclization of 2-alkynylaldehyde cyclic acetals has been developed for the synthesis of indenone derivatives. A wide variety of functionalized indenone derivatives can be obtained in good-to-excellent yields. HMBC and NOESY NMR analyses and mechanistic elucidation experiments revealed that the cyclization occurs via a 1,5-H shift. The cyclic acetal group promoted the 1,5-H shift by activating the benzylic C-H bond and preventing the migration of the alkoxy group by tethering both alkoxy groups.
Gesehen am 20.04.2020